The cardiometabolic conditions of psoriatic disease - Toussirot, Eric; Gallais-Sérézal, Irène; Aubin, François (Frontiers in Immunology, 2022)
Psoriasis (PsO) and psoriatic arthritis (PsA), together known as psoriatic disease (PsD), are immune-mediated diseases with a chronic and relapsing course that affect the skin, the joints or both. The pathophysiology of PsO is complex and involves abnormal expression of keratinocytes and infiltration of the skin with dendritic cells, macrophages, neutrophils and T lymphocytes. Around 30% of patients with PsO develop arthritis with axial and/or peripheral manifestations. Both PsO and PsA share similar Th1- and Th17-driven inflammation, with increased production of inflammatory cytokines, including TNFα, IFN-γ, IL-17, IL-22, IL-23 in the skin and the synovial membrane. PsD is associated with a high burden of cardiometabolic diseases such as hypertension, diabetes, dyslipidemia, obesity, metabolic syndrome and cardiovascular (CV) complications as compared to the general population. These comorbidities share common immunopathogenic pathways linked to systemic inflammation, and are associated with the extent and severity of the disease. Morever, they can influence treatment outcomes in PsD. In this short review, we summarize the available evidence on the epidemiology, clinical aspects and mechanisms of cardiometabolic conditions in patients with PsD. We also discuss the impact of targeted treatments such as methotrexate and biological agents on these cardiometabolic conditions.